2023
DOI: 10.1111/jomf.12919
|View full text |Cite
|
Sign up to set email alerts
|

Parental incarceration and parent–youth closeness

Abstract: ObjectiveThe goal of this study is to examine the association between parental incarceration and parent–youth closeness.BackgroundDespite the established complex repercussions of incarceration for relationships between adults, and the well‐known intergenerational consequences of parental incarceration, little is known about how incarceration structures intergenerational relationships between parents and children.MethodsIn this article, I use data from the Future of Families and Child Wellbeing Study (N = 3408)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…No evidence of a relationship between paternal incarceration and mother-child relationship quality was found. These findings are consistent with previous research showing that father-child and father-mother relationships, are negatively affected by paternal incarceration, but mother-child relationships are not (Turney, 2023;Turney & Wildeman, 2013). Earlier research has also shown that the negative impact for family relationships is concentrated among families with more positive relationships before imprisonment (Turanovic et al, 2012;Turney, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…No evidence of a relationship between paternal incarceration and mother-child relationship quality was found. These findings are consistent with previous research showing that father-child and father-mother relationships, are negatively affected by paternal incarceration, but mother-child relationships are not (Turney, 2023;Turney & Wildeman, 2013). Earlier research has also shown that the negative impact for family relationships is concentrated among families with more positive relationships before imprisonment (Turanovic et al, 2012;Turney, 2023).…”
Section: Discussionsupporting
confidence: 92%